Avaliação do índice inflamatório da dieta e marcadores biológicos da inflamação após intervenção nutricional com restrição do tempo de alimentação - Paula Duarte Palhares (2023)
Intermittent fasting has emerged as a promising approach, evolving as a potential tool to assist in weight loss and the optimization of metabolic health, particularly in cases of overweight and obesity. Previous work from our research group conducted a randomized clinical trial to evaluate the effectiveness of calorie restriction, either alone or combined with time-restricted eating (TRE), in weight loss for women with overweight and obesity. Participants who underwent TRE exhibited greater weight loss, however, no apparent factor evaluated was identified as a driver of this improved response. The aim of this study was to investigate whether diet characteristics, based on the dietary inflammatory index (DII), biological markers of inflammation, or energy expenditure, determine the best response for weight loss in participants subjected to calorie restriction combined with time-restricted eating compared to calorie restriction alone. This work was divided into two axes. The first used a sample from a parallel randomized clinical trial, consisting of adult women aged 18 to 59 years, with a body mass index (BMI) of 25 kg/m² or higher. The study protocol eating hours, lasting approximately two months. The dietary inflammatory index was calculated from the three-day food records of each participant, encompassing 26 dietary parameters, including macronutrients, micronutrients, and calories. Isolation of human peripheral blood mononuclear cells was performed using Ficoll-Paque™ Plus reagent (GE Healthcare, Uppsala, Sweden), and total RNA extraction from these cells for analysis of inflammatory cytokine gene expression was done by reverse transcription-polymerase chain reaction (RT-PCR) using the RNeasy Mini Kit (Qiagen, Hilden, Germany). Data were analyzed with the aid of the Statistical Package for the Social Sciences® (SPSS) version 20.0 (IBM Corp., Armonk, NY, USA). The Shapiro-Wilk test was used to assess the normality of quantitative variables. The Generalized Estimating Equations (GEE) method was used for the analysis of longitudinal repeated measures data, assessing the effect of time and intervention separately, and the time x intervention interaction. The Bonferroni post-hoc test was used to detect significant differences identified by GEE. The second axis used the sample from this and another non-randomized clinical trial, consisting of adult women, aged 18 to 59 years, either eutrophic, with a BMI greater than 18.5 kg/m² up to 24.99 kg/m², or obese, with a BMI greater than 35 kg/m². Participants attended the clinic after overnight fasting to perform indirect calorimetry testing. Subsequently, they received a standard breakfast and were released to continue their daytime activities. Participants were advised not to consume anything else during the day and returned to the clinic 10 hours later for another indirect calorimetry assessment. The same statistical analysis method from axis 1 was used. The results demonstrate that none of the groups presented an anti-inflammatory diet profile at the end of the intervention, with no difference between the groups, although in both groups the dietary prescription determined lower indices compared to baseline. No significant correlations were found between the DII and serum concentrations of the cytokines IL-10, IL-18, TNF, and MCP-1 in both groups. The relative expression of NFκB in PBMC did not show a significant difference between the groups. However, significant interactions were found between the relative expression of NFκB and the serum concentration of TNF in the group without TRE after 30 days of intervention. After 60 days, there were significant time-by-intervention interactions between the relative expression of NFκB and IL-18 in both groups. The results indicate that the DII and biological markers of inflammation did not have a significant impact on the differentiated weight loss of patients in TRE. Furthermore, the analysis of resting energy expenditure corrected for fat-free mass showed no significant difference between the times of intervention in both groups, in both studies evaluated.